A model for Malaysian public universities. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
The Department of Higher Education Management (IP IPT) and the Minis Lry of Higher Education (KPT) Malaysia have requested the help of the National Higher Education Research Institute (IPPTN) to study and subsequently to recommend a model for Malaysian public universities.